Modern architecture, empire, and race in fascist Italy - McLaren, Brian (Spatial practices, 2021)
"This book explores the relationship between architecture and race that lingered beneath the surface of the author's previous research- beginning with his dissertation on modernity and indigenous culture in Italy's North African colonies in the History, Theory and Criticism Section"--